Structure of a Murine Norovirus NS6 Protease-Product Complex Revealed by Adventitious Crystallisation - Leen, Eoin N.; Baeza, Gabriela; Curry, Stephen (PLOS ONE, 2012)
Murine noroviruses have emerged as a valuable tool for investigating the molecular basis of infection and pathogenesis of the closely related human noroviruses, which are the major cause of non-bacterial gastroenteritis. The replication of noroviruses relies on the proteolytic processing of a large polyprotein precursor into six non-structural proteins (NS1–2, NS3, NS4, NS5, NS6pro, NS7pol) by the virally-encoded NS6 protease. We report here the crystal structure of MNV NS6pro, which has been determined to a resolution of 1.6 Å. Adventitiously, the crystal contacts are mediated in part by the binding of the C-terminus of NS6pro within the peptide-binding cleft of a neighbouring molecule. This insertion occurs for both molecules in the asymmetric unit of the crystal in a manner that is consistent with physiologically-relevant binding, thereby providing two independent views of a protease-peptide complex. Since the NS6pro C-terminus is formed in vivo by NS6pro processing, these crystal contacts replicate the protease-product complex that is formed immediately following cleavage of the peptide bond at the NS6-NS7 junction. The observed mode of binding of the C-terminal product peptide yields new insights into the structural basis of NS6pro specificity.